THE VARIABILITY OF ACCOUNTING STANDARDS: TOOL UNLIMITED MANIPULATION OR FLEXIBLE OPTION ACCOUNTING REFLECTION - E. Nemtsova; E. Mezentseva (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the study of the polarization of accounting thought in relation to the multivariate mechanism ofconstruction of the accounting model, which led to the development of ambiguous in nature specific accounting technology - creative accounting.